The Association of Serum Sodium Levels with Intraventricular Hemorrhage in Preterm Infants: A Prospective Longitudinal Study from Pakistan - Bhanbhro, Bakhtiar Ahmed; Bharo, Mumtaz Ali; Baloach, Kamran Ali Shahani; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the association of hypernatremia with intraventricular haemorrhage in preterm infants in a local setting. Study Design: Prospective longitudinal study. Place and Duration of Study: Neonatal Intensive Care Units (NICU), Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat Khaipur Mirs from Sep 2018 to Mar 2020. Methodology: All the infants with the gestational age of <32 weeks of pregnancy were included, while infants who died <12 hours of life were excluded from the study. All relevant maternal and neonatal data were extracted from patient files and recorded in electronic form. The infants were further stratified into three groups: i) infants without intraventricular haemorrhage, ii) mild intraventricular haemorrhage, and iii) severe intraventricular haemorrhage. Results: The intraventricular haemorrhage was 40%. 84 (29.2%) infants had a mild intraventricular haemorrhage, and 32 (11.1%) had a severe intraventricular haemorrhage. The highest sodium level was 145.91 ± 6.98 mEq/L and 143.51 ± 5.93mEq/L in the mild IVH and severe intraventricular haemorrhage groups, respectively. The fluctuations in serum sodium levels from week 1 to week 2 were significantly more prominent in infants without intraventricular haemorrhage compared to intraventricular haemorrhage groups (12.31 ± 6.67 mEq/L, 10.11 ± 9.32 mEq/L, and 6.54 ± 7.53 mEq/L, respectively; p:0.001). Conclusion: The fluctuation of serum sodium in infants with severe Intraventricular haemorrhage was significantly greater than in infants with mild intraventricular haemorrhage or without intraventricular haemorrhage.